Integrasi Nilai-Nilai Pancasila dalam Pembelajaran PKN untuk Pembentukan Karakter Siswa Sekolah Dasar - Mardin, Laode; Zarkasih, Khamim (LPPM IAIN Sorong, 2025)
Pancasila and Citizenship Education (PKn) has an important role in character building of students in elementary schools. This study aims to examine the integration of Pancasila values ​​in PKn learning and its impact on the development of students' character. The approach used in this study is qualitative with a literature study method. Data were collected from various articles, journals, and reliable sources, the criteria for selecting literature covered the period 2015-2024, relevance to the topic of character education and PKn, and sources from accredited journals. Of the several literatures analyzed, some came from international journals, while others were from national sources that discussed character education through PKn in elementary schools. The results of the study showed that the integration of Pancasila values, such as discipline, mutual cooperation, tolerance, and love for the country, can be done through various methods, including learning in and out of class, role models, and extracurricular activities. Therefore, to achieve success in character building, it is necessary to make modifications in the learning approach by prioritizing the integration of character values ​​as a whole. This research provides an important contribution to the development of more effective citizenship education in forming quality and nationalistic student characters.